AN ANALYSIS OF TEACHER’S PROFESSIONAL COMPETENCE IN TEACHING ENGLISH AT SMKN 1 BABAU - Hanafiah, Wa Ode; Syafitri, Nining; Al-Husaini, Ainun Khalifah (English Education Journal, 2024)
Problem statement of this research was wheter the english teacher for class XI at SMKN 1 Baubau was professional according to the competence standar of the teaching professional. To find out the teacher’s professional in teaching english language learning. This research used a mix method, namely a combination of qualitative and quanitative methods. Instrumens used were interview and questionnaire. The data analysis tecnique used in this research, in analyzing the research of interview data using data reduction and analyzing the research questionnaire was carried out in several steps, namely using Microsoft Exel 2019, descriptive with SPSS version 26.0. analysis of research data interview showed that the XI class english teachers had implemented professional competence and research data form questionnaire, the english teachers for class XI was alredy professional met teachers qualifications teachers competence standars adapted from the Regulation of the Minister of National Education of the Republic of Indonesia No.16 of 2007.